Impact of the Updated World Health Organization Guideline on Hemoglobin Cutoffs on National Anemia Prevalence Estimates in 6–59-month-old Indian Children - Tinku Thomas; Anura Viswanath Kurpad; Santu Ghosh; Harshpal Singh Sachdev (Indian Journal of Public Health)
The World Health Organization has recently lowered the hemoglobin (Hb) diagnostic cutoff for anemia in 6–23-month-old children by 0.5 g/dL and specifies the use of venous blood. The national prevalence of anemia defined from venous blood in children 6–23 months reduced by ~10% points when using the new Hb cutoff.